The Dead Sea scrolls rewriting Samuel and Kings : texts and commentary - Feldman, Ariel, 1974- (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2015)
Long neglected by scholars, the Dead Sea scrolls rewriting Samuel-Kings shed precious light on the ancient Jewish interpretation of these books. This volume brings all these texts together for the first time under one cover. Improved editions of the fragments, up-to-date commentary, and detailed discussions of the exegetical traditions embedded in these scrolls will be of interest to both scholars and students of Second Temple Jewish literature.